Exacerbation of Autoantibody-Mediated Hemolytic Anemia by Viral Infection - Meite, Mory (American Society for Microbiology, 2000)
Strong enhancement of the pathogenicity of an antierythrocyte monoclonal antibody was observed after infection of mice with lactate dehydrogenase-elevating virus. While injection of the antierythrocyte antibody alone induced only moderate anemia, concomitant infection with this virus, which is harmless in most normal mice, led to a dramatic drop in the hematocrit and to death of infected animals. In vitro and in vivo analyses showed a dramatic increase in the ability of macrophages from infected mice to phagocytose antibody-coated erythrocytes. These results indicate that viruses can trigger the onset of autoimmune disease by enhancing the pathogenicity of autoantibodies. They may explain how unrelated viruses could be implicated in the etiology of autoantibody-mediated autoimmune diseases.